Genetic characterization and antimicrobial profiling of bacterial isolates collected from Nile tilapia (Oreochromis niloticus) affected by summer mortality syndrome - Ali, Shimaa E.; Mahana, O.; Mohan, Chadag V.; Delamare-Deboutteville, Jerome; Elgendy, M.Y. (Wiley, 2022)
In recent years, Egyptian tilapia aquaculture has experienced mortality episodes during the summer months. The causative agents responsible for such mortalities have not been clearly identified. A total of 400 fish specimens were collected from affected tilapia farms within five Egyptian governorates. A total of 344 bacterial isolates were identified from the examined fish specimens. Bacterial isolates were grouped into seven genera based on API 20E results. The most prevalent pathogens were Aeromonas spp. (42%), Vibrio spp. (21%), and Streptococcus agalactiae (14.5%). Other emerging infections like, Plesiomonas shigelloides (10%), Staphyloccocus spp. (8%), Pseudomonas oryzihabitans, and Acinetobacter lwoffii (2.3%) were also detected. Sequence analysis of the 16S ribosomal RNA bacterial gene of some isolates, confirmed the phenotypic identification results. The analysis of antibiotic resistance genes revealed the presence of aac(6′)-Ib-cr (35.7%), blaCTX gene (23.8%), qnrS (19%), ampC (16.7%), floR (14.3%), sul1, tetA, and van.C1 (2.4%) genes in some isolates. The antimicrobia resistance gene, qac was reported in 46% of screened isolates. Bacterial strains showed variable virulence genes profiles. Aeromonas spp. harboured (act, gcat, aerA, lip, fla, and ser) genes. All Vibrio spp. possessed the hlyA gene, while cylE, hylB, and lmb genes, were detected in S. agalactiae strains. Our findings point to the possible role of the identified bacterial pathogens in tilapia summer mortality syndrome and highlight the risk of the irresponsible use of antibiotics on antimicrobial resistance in aquaculture.